Bioactive compounds from marigold processing waste: Extraction, isolation, and antidiabetic activity - Nellippatta Deepika, Basavan Duraiswamy, Salma Khanam, Divanji Maohar, Hebbani Nagarajappa Shivaprasad, Tripathy Amrutanand (Journal of Applied Pharmaceutical Science, 2023)
Diabetes is a chronic metabolic disorder characterized by excessive blood sugar levels. According to the International Diabetes Federation, 537 million adults are living with diabetes today and is projected to rise to 643 million by 2030 and 783 million by 2045. Marigold or Tagetes erecta Linn. is a common plant used in diverse cultures in India. Different parts of this plant are used in folk medicine to treat colic, diarrhea, vomiting, fever, skin diseases, and hepatic disorders. During marigold cultivation, the leaves are the most common agricultural waste. In the present study, we aim to evaluate the in-vitro antidiabetic activity of hydroalcoholic extract of leaves of marigold and the isolation and characterization of active constituents. The hydroalcoholic extract was fractionated by column chromatography using different stationary phases and solvents ranging from highly non-polar to polar as mobile phase by gradient elution method. In-vitro alpha-glucosidase inhibition of the hydroalcoholic extract and isolated compounds was performed and compared with the standard drug acarbose. The isolated compounds were tentatively characterized as kaempferol di-O-rhamnoside (compound 1), kaempferol O-rhamnoside-O-pentoside (compound 2), and kaempferol O-rhamnoside (compound 3). The isolated compounds were more active than the hydroalcoholic extract. Kaempferol O-rhamnoside was found to possess the highest antidiabetic activity with an IC50 value of 61 μg/ml.